2006
DOI: 10.1016/j.tet.2006.05.078
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and kinetic investigation of the selective acidolysis of para-substituted N-benzyl- or N-phenyl-N-phenylacetyl-α,α-dialkylglycine cyclohexylamides

Abstract: Several derivatives of N-phenylacetyl-N-benzyl-α,α-dimethylglycine cyclohexylamide and their α,α-dibenzylglycine analogues were synthesised by a Ugi-Passerini reaction. In addition, a few analogues of the former but having an N-phenyl instead of a benzyl group at the nitrogen atom were synthesised. The compounds in each of these three sets differed from each other at the position 4 of the N-benzyl (and N-phenyl) group. These adducts were submitted to acidolysis with TFA to obtain the corresponding free acids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…They concluded that the acidolysis of the C-terminal amide bond depends mostly on polar substituent parameters rather than steric. In addition, they achieved the isolation of an oxazolone derivative, thereby confirming Goodman’s proposal and demonstrating that amide cleavage proceeds through a cyclic intermediate [ 15 ]. A similar behavior was also observed for N -acylated peptoids, which trigger the loss of peptoid monomer from the sequence, a phenomenon also explained through an oxazolinium-based mechanism [ 16 ].…”
Section: Introductionsupporting
confidence: 53%
“…They concluded that the acidolysis of the C-terminal amide bond depends mostly on polar substituent parameters rather than steric. In addition, they achieved the isolation of an oxazolone derivative, thereby confirming Goodman’s proposal and demonstrating that amide cleavage proceeds through a cyclic intermediate [ 15 ]. A similar behavior was also observed for N -acylated peptoids, which trigger the loss of peptoid monomer from the sequence, a phenomenon also explained through an oxazolinium-based mechanism [ 16 ].…”
Section: Introductionsupporting
confidence: 53%
“…In addition, the use of ketones or ketimines as substrates in such reactions, in order to generate structures bearing tetrasubstituted carbons, entails additional obstacles, since the inherent steric factors observed in these systems enhance the difficulty level in these synthetic methodologies [ 23 ]. In addition, the use of acyclic ketones typically requires preformation of the imine intermediate in a separate step, and the yields of the Ugi are often modest [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This difficulty can only be overcome by taking advantage of synthetic methodologies not usually used in peptide chemistry, such as the methodology based on the Ugi reaction, which we have been developing over the last decade. [17][18][19][20] Several studies on the biological activity of N-methyl, C α,α -dimethylglycine, (Me-Aib) have been reported. Me-Aib has been widely used as a specific model substrate for system A amino acid transport, 21 which is expressed strongly in transformed and malignant cells.…”
mentioning
confidence: 99%